ChemInform Abstract: Emerging Technologies for Metabolite Generation and Structural Diversification. Issue 51 (17th December 2013) - Cusack, Kevin P.; Koolman, Hannes F.; Lange, Udo E. W.; Peltier, Hillary M.; Piel, Isabel; Vasudevan, Anil
Abstract Review: about 100 refs.